Defining Radiation Belt Enhancement Events Based on Probability Distributions - Geoffrey D. Reeves; Elizabeth M. Vandegriff; Jonathan T. Niehof; Steven K. Morley; Gregory S. Cunningham; Michael G. Henderson; Brian A. Larsen (Space Weather)
Abstract We present a methodology to define moderate, strong, and intense space weather events based on probability distributions. We have illustrated this methodology using a long‐duration, uniform data set of 1.8–3.5 MeV electron fluxes from multiple LANL geosynchronous satellite instruments, but a strength of this methodology is that it can be applied uniformly to heterogeneous data sets. It allows quantitative comparison of data sets with different energies, units, orbits, and so forth. The methodology identifies a range of times, “events,” using variable flux thresholds to determine average event occurrence in arbitrary 11‐year intervals (“cycles”). We define moderate, strong, and intense events as those that occur 100, 10, and 1 time per cycle and identify the flux thresholds that produce those occurrence frequencies. The methodology does not depend on any ancillary data set (e.g., solar wind or geomagnetic conditions). We show event probabilities using GOES > 2 MeV fluxes and compare them against event probabilities using LANL 1.8–3.5 MeV fluxes. We present some examples of how the methodology picks out moderate, strong, and intense events and how those events are distributed in time: 1989 through 2018, which includes the declining phases of solar cycles 22, 23, and 24. We also provide an illustrative comparison of moderate and strong events identified in the geosynchronous data with Van Allen Probes observations across all L‐shells. We also provide a catalog of start and stop times of moderate, strong, and intense events that can be used for future studies.